Law No. 150 of the year 2021 Amending Certain Provisions of the Penal Code = قانون رقم 150 لسنة 2021 بتعديل بعض أحكام قانون العقوبات - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic